Does Corporate Social Responsibility Influence Firm Performance of Indian Companies? - Mishra, Supriti (Journal of business ethics, 2010)
This study examines whether corporate social responsibility (CSR) towards primary stakeholders influences the financial and the non-financial performance (NFP) of Indian firms. Perceptual data on CSR and NFP were collected from 150 senior-level Indian managers including CEOs through questionnaire survey. Hard data on financial performance (FP) of the companies were obtained from secondary sources. A questionnaire for assessing CSR was developed with respect to six stakeholder groups – employees, customers, investors, community, natural environment, and suppliers. A composite measure of CSR was obtained by aggregating the six dimensions. Findings indicate that stock-listed firms show responsible business practices and better FP than the non-stock-listed firms. Controlling confounding effects of stock-listing, ownership, and firm size, a favorable perception of managers towards CSR is found to be associated with increase in FP and NFP of firms. Such findings hold good when CSR is assessed for the six stakeholder groups in aggregate and for each stakeholder group in segregate. Findings suggest that responsible business practices towards primary stakeholders can be profitable and beneficial to Indian firms.